Eloquence in an electronic age - Kathleen Hall Jamieson (Oxford University Press, 1988)
In a book that blends anecdote with analysis, Kathleen Hall Jamieson--author of the award-winning Packaging the Presidency--offers a perceptive and often disturbing account of the transformation of political speechmaking